2000
DOI: 10.1016/s0741-5214(00)70080-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of endothelial cells and their progenitor cells from human peripheral blood

Abstract: We conclude that endothelial progenitor cells can be isolated from human adult peripheral and umbilical cord blood and developed into EC cultures as a source of cells for vascular graft seeding and gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 26 publications
2
76
0
3
Order By: Relevance
“…106 Heterologous, homologous, or autologous EPCs administered systemically to animals with operatively induced hindlimb ischemia were found to incorporate themselves into foci of neovascularization in ischemic muscles of the affected hindlimb. These findings, together with those of other recent studies, [107][108][109][110] have been interpreted as evidence of postnatal "vasculogenesis." 101,105 …”
Section: Postnatal Vasculogenesissupporting
confidence: 82%
“…106 Heterologous, homologous, or autologous EPCs administered systemically to animals with operatively induced hindlimb ischemia were found to incorporate themselves into foci of neovascularization in ischemic muscles of the affected hindlimb. These findings, together with those of other recent studies, [107][108][109][110] have been interpreted as evidence of postnatal "vasculogenesis." 101,105 …”
Section: Postnatal Vasculogenesissupporting
confidence: 82%
“…30 Since the original report several other groups, including ours, have confirmed the original finding and have reported various modifications of the methods for the isolation, characterization, and culture of EPCs. 9,23,[31][32][33] The cells are thought to originate from a common hemangioblast precursor in the bone marrow; 9,33,34 however, nonhematopoietic mesenchymal precursors in the bone marrow (multipotent adult progenitor cells) have also been reported to transdifferentiate into EPCs in culture. 35 Other studies have reported that myeloid/monocyte lineage cells (CD14 ϩ ) can differentiate into cells with EPC characteristics.…”
Section: Isolation Characterization and Genetic Modification Of Epcsmentioning
confidence: 99%
“…Typically, the cells are defined on the basis of expression of cell surface markers such as CD34, Flk-1, and CD-133. 30,31 The cells have high proliferative potential, albeit for a finite number of cell divisions. 10,19 -21,30,34 As the cells differentiate, they acquire endothelial lineage markers, vascular endothelium-cadherin, PECAM-1 (CD31), von Willebrand factor, endothelial nitric oxide synthase (eNOS), and E-selectin, and incorporate acetylated low-density lipoprotein cholesterol.…”
Section: Isolation Characterization and Genetic Modification Of Epcsmentioning
confidence: 99%
“…EPCs are a small population of progenitor cells that reside in bone marrow and, upon stimulation, are released into circulating peripheral blood [7][8][9][10][11]. Once in circulation, EPCs are thought to migrate to sites of vascular injury and are involved in vasculogenesis [12].…”
Section: Introductionmentioning
confidence: 99%